Analisis Faktor-Faktor Yang Memengaruhi Kepercayaan Dan Resiko Pengguna Dalam Bertransaksi Pada E-Commerce XYZ Menggunakan UTAUT (Unified Theory Of Acceptance And Use Of Technology) - Muhammad Zainul Mubarok; Ari Kusyanti; Himawat Aryadita (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In Indonesia, e-commerce is getting more popular since a lot of online stores occurred in the current digital industry. One of the growing e-commerce in Indonesia is E-Commerce XYZ. It offers various products and services such as electronic devices, beauty products, household stuffs, and many more. This research is conducted to learn the leverage factors of consumer's decision on doing a transaction in Elevania. The research used Unified Theory Acceptance and Use of Technology (UTAUT) model while added trust and risk factor. The variables of the research are consumer trust, perceived risk, performance expectancy, social influence, effort expectancy, facilitating conditions, and behavioral intention. Analysis technique used multiple linier regression. The research finally found that partially, only consumer trust and social influence factor have significant positive leverage toward behavioral intention. Meanwhile, all factors simultaneously have significant leverage toward behavioral intention